Distortion Correction for 3D Scan of Trunk Swaying Human Body Segments - Funatomi, Takuya; Iiyama, Masaaki; Kakusho, Koh; Minoh, Michihiko (ELCVIA Electronic Letters on Computer Vision and Image Analysis, 2009)
We propose a method for acquiring a 3D shape of human body segments accurately. Using a light stripe triangulation range finder, we can acquire accurate 3D shape of a motionless object in dozens of seconds. If the object moves during the scanning, the acquired shape would be distorted. Naturally, humans move slightly for making balance while standing even if the subject makes an effort to stay still for avoiding the distortion in acquired shape. Our method corrects the distortion based on measured subject’s motion during the scanning. Experimental results show the accuracy of the proposed method. Trunk swaying degrades the accuracy of the light stripe triangulation from 1mm to 10mm. We can keep the accuracy of as good as 2mm by applying our method.